(untitled) (Journal of the College of Basic Education, 2022)
Through the field researcher’s observation of the level of performance of female students in the skill of scoring in handball, she noticed that there is a discrepancy in the level of female students in learning the skill of scoring in handball, which may be due to the difficulty of this skill or following traditional teaching methods when learning it, which may not lead to stimulating their motivation to learn that skill. Therefore, the researcher’s idea came to use the strategy of concept maps in teaching this skill, which may stimulate motivation and desire among students towards learning and try to overcome some deficiencies when learning this skill. One of the research objectives was to identify the differences in learning some types of handball scoring. As a result of using the concept maps strategy and for the control and experimental groups, the researcher assumed several hypotheses, among which there were